Nepal’s Diplomacy through Rhetorics at UNGA - Sharma, Bimala (Journal of Foreign Affairs, 2023)
The paper concentrates on investigating Nepal’s Diplomacy through rhetorics. To do so the discourse of the diplomatic speeches presented by Nepal in UN general assembly are critically examined. A special category of communication known as the language of diplomacy is employed in all kind diplomatic endeavors. Diplomatic language is formal, accurate, disciplined, and is mindful of its use of grammar, syntax, and vocabulary to make it easier for people of all nationalities and cultures to communicate clearly and effectively. Euphemisms or indirect language is employed to communicate to avoid aggressive language which can be offensive. Respecting all cultures is must hence diplomatic language is culturally sensitive. Diplomatic discourse is fundamental device to cultivate global cooperation and resolve differences. The paper essences on primarily exploring the speeches of Nepal’s Statespersons: Minister of Foreign Affairs Chuda Nath Sharma (1958), Prime Ministers BP Koirala (1960),Prime Minister Kirtinidhi Bist (1968) and Sailendra Kumar Upadhyay (1988) at UN General Assemblies respectively from the lenses of critical discourse analysis. Hence, it confines itself within the speeches (the selected primary texts), their rhetorical patterns, contents delivered through diplomatic language, their domestic ideology and power politics.